2013
DOI: 10.1007/s12028-013-9854-x
|View full text |Cite
|
Sign up to set email alerts
|

What is Specialized Care in Status Epilepticus and in Which ICU?

Abstract: Status epilepticus (SE) is a serious, potentially life-threatening condition. The outcome of SE is variable, while some patients may present neurological deficits, others recover without sequellae. The reasons for these different outcomes are not fully understood, but some prognostic factors have been identified, such as the age, the clinical type of SE, a previous history of epilepsy, the etiology, and the delay of treatment onset [1][2][3].Despite being an important stage in the treatment, there have been ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…One study showed that, for status epilepticus, more continuous electroencephalograms (EEGs) were ordered in the neuroICU, and fewer patients were intubated, but more eventually received tracheostomies compared with medical ICU admission. No significant differences were found in mortality, LOS, and outcome at discharge; however, the heterogeneity of status epilepticus limits direct comparison, and more research to evaluate expected benefits of status epilepticus management in a neuroICU is justified . A benefit for neuroICU care may be shown for various other disease processes, such as cerebral venous sinus thrombosis: after institution of continuous neuroICU coverage, outcomes improved in a recent single-institution experience …”
Section: Neurocritical Care and Outcomesmentioning
confidence: 99%
“…One study showed that, for status epilepticus, more continuous electroencephalograms (EEGs) were ordered in the neuroICU, and fewer patients were intubated, but more eventually received tracheostomies compared with medical ICU admission. No significant differences were found in mortality, LOS, and outcome at discharge; however, the heterogeneity of status epilepticus limits direct comparison, and more research to evaluate expected benefits of status epilepticus management in a neuroICU is justified . A benefit for neuroICU care may be shown for various other disease processes, such as cerebral venous sinus thrombosis: after institution of continuous neuroICU coverage, outcomes improved in a recent single-institution experience …”
Section: Neurocritical Care and Outcomesmentioning
confidence: 99%
“…Although SRSE has a poor prognosis, some patients may recover even in prolonged cases. Advice by and/or transfer to centres with specific neurology expertise are advisable [77].…”
Section: Caring For the Injured Brain: Management Of Specific Patholomentioning
confidence: 99%